The Effect of Implementing Flipped Classroom on Highschool Students’ Reading Skill - Refianisya Rachmanda; Hanafi; Henri Fatkurochman (Institut Agama Islam Tarbiyatut Tholabah, 2026)
In this research the research problem formulated is “is there any significant effect of implementing flipped classroom on high school students’ reading skill?” and the objective of this research to find out whether there is a significant effect of implementing flipped classroom on high school students’ reading skill. Based on research problem and relevant theory the hypothesis of this research is there is an significant effect of implementing flipped classroom on high school students.VThe research design of this research used quasi experimental research design. The research subject are XI-G and XI-J in MAN 2 Jember that each of class consisting of 35 students (N=70). The data are collected by pre test and post-test and the research instrument used reading test in order to analyze the students reading score. All students participating active during the teaching and learning activities and students in experiment class become more confident because the already learned the material via online before the learning activities in the class. The result of the post test scores are analyzed use Mann Whitney U Test and the result is 0,031 and it was less than 0,05 (0,001 < 0,05), Based on the research result, it can be concluded that students’ reading text is significantly affected by implementing flipped classroom method